2009
DOI: 10.1523/jneurosci.0967-09.2009
|View full text |Cite
|
Sign up to set email alerts
|

Reliable Coding Emerges from Coactivation of Climbing Fibers in Microbands of Cerebellar Purkinje Neurons

Abstract: The inferior olive projects climbing fiber axons to cerebellar Purkinje neurons, where they trigger calcium-based dendritic spikes. These responses dynamically shape the immediate spike output of Purkinje cells as well as provide an instructive signal to guide long-term plasticity. Climbing fibers typically fire approximately once a second, and the instructive role is distributed over many such firing events. However, transmission of salient information on an immediate basis needs to occur on a shorter timesca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

23
170
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 113 publications
(193 citation statements)
references
References 62 publications
23
170
0
Order By: Relevance
“…The spatial extension of the set of PCs excited by our smallest illumination (around 300 μm diameter) is closer to the scale of cerebellar zones than of microzones (11). Indeed, recent imaging studies in vivo describing synchronized CSs during sensory stimulation identified microbands narrower than 100 μm (37,38). Testing whether the control of the CS is segregated across such microzones may require the use of specific strategies (39) to restrict the expression of the opsin to single microzones and therefore circumvent the difficulty of illuminating very narrow bands of cells.…”
Section: Discussionmentioning
confidence: 69%
“…The spatial extension of the set of PCs excited by our smallest illumination (around 300 μm diameter) is closer to the scale of cerebellar zones than of microzones (11). Indeed, recent imaging studies in vivo describing synchronized CSs during sensory stimulation identified microbands narrower than 100 μm (37,38). Testing whether the control of the CS is segregated across such microzones may require the use of specific strategies (39) to restrict the expression of the opsin to single microzones and therefore circumvent the difficulty of illuminating very narrow bands of cells.…”
Section: Discussionmentioning
confidence: 69%
“…It is known from in vivo imaging and multielectrode array measurements that temporally correlated complex spikes occur in parasagittally oriented modules of PNs within the cerebellar cortex (40)(41)(42)(43), and recent evidence is consistent with the idea that the CF-associated teaching signal is encoded by temporally correlated complex spike activity (44). The axons of PNs are inhibitory and converge on single DCN neurons, thus prolonged post-CxSp pauses occurring synchronously in a module of PNs could provide an extended window of disinhibition to the DCN cells receiving such input (45,46).…”
Section: Discussionmentioning
confidence: 99%
“…This result also implies that the sensory inputs provided by inferior olive neurons through CFs rely on their precise timing and the spatiotemporal activation patterns in the local population of Purkinje cells Sasaki et al, 1989;Ozden et al, 2009;Schultz et al, 2009) in order for them to be discriminated from spontaneous CF input.…”
Section: Modulation Of Dendriticmentioning
confidence: 97%
“…Although CF-evoked dendritic Ca 2ϩ signals have been detected in vivo using bulk loading or electroporation of [Ca 2ϩ ] indicators into Purkinje cells (Sullivan et al, 2005;Mukamel et al, 2009;Ozden et al, 2009;Schultz et al, 2009;Chen et al, 2010), quantitative characterization of the magnitude and spatial spread of the Ca 2ϩ signals and their precise relationship with electrical activity has thus far only been possible in vitro (Konnerth et al, 1992;Miyakawa et al, 1992;Wang et al, 2000). It is crucial to obtain this information in vivo, particularly given that dendritic excitability can be modulated by action potential firing, background excitatory and inhibitory synaptic input, and activity in neuromodulatory afferents.…”
Section: Introductionmentioning
confidence: 99%